FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA DPRK DALAM PENGAWASAN KEUANGAN DAERAH DENGAN KOMITMEN PROFESIONAL SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA DPRK KABUPATEN ACEH UTARA) - Putri, Rani Gesta (Jurnal Akuntansi dan Keuangan, 2020)
The objective of this research was to find out: 1) the influence of the parliamentarians’ knowledge of budget, personal background, political background, public accountability, community participation, and public policy transparency on the performance of DPRK (Regency Parliament) in regional financial monitoring; 2) that professional commitment is able to become moderating variable to the relationship of the parliamentarians’ knowledge on budget, personal background, political background, public accountability, community participation, and public policy transparency with the performance of DPRK in the regional financial monitoring. This research applied quantitative method. It was carried out in October 2018 at the DPRK of North Aceh Regency with term of office from 2014 to 2019. The data were collected through questionnaires distributed to 45 respondents who are members of DPRK of North Aceh Regency by using census technique. The data analysis was performed using reliability and validity tests, classic assumption test, multiple linear regression methods and residual test by means of SPSS. The result of this research showed 1) that the parliamentarians’ knowledge on budget, personal background, political background, public accountability, community participation, and public policy transparency simultaneously influenced the performance of the DPRK in the regional financial monitoring, and 2) that professional commitment was not able to become the moderating variable to the relationship of the parliamentarians’ knowledge on budget, personal background, political background, public accountability, community participation, and public policy transparency with the performance of DPRK in the regional financial monitoring.